SIRT1-Related Signaling Pathways and Their Association With Bronchopulmonary Dysplasia - Yang, Kun; Dong, Wenbin (Frontiers in Medicine, 2021)
Bronchopulmonary dysplasia (BPD) is a chronic and debilitating disease that can exert serious and overwhelming effects on the physical and mental health of premature infants, predominantly due to intractable short- and long-term complications. Oxidative stress is one of the most predominant causes of BPD. Hyperoxia activates a cascade of hazardous events, including mitochondrial dysfunction, uncontrolled inflammation, reduced autophagy, increased apoptosis, and the induction of fibrosis. These events may involve, to varying degrees, alterations in SIRT1 and its associated targets. In the present review, we describe SIRT1-related signaling pathways and their association with BPD. Our intention is to provide new insights into the molecular mechanisms that regulate BPD and identify potential therapeutic targets for this debilitating condition.